2019
DOI: 10.5455/javar.2019.f320
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal parasites of different avian species in Ilorin, North Central, Nigeria.

Abstract: Objective: The current study aimed to determine the prevalence, infection burden, and risk factors associated with the occurrence of gastrointestinal (GI) parasites in different avian species in Ilorin, Nigeria. Materials and Methods: This study was conducted in Ilorin, involving 597 fecal samples and GI tracts from a variety of sold and slaughtered avian species. The study was conducted between September 2017 and February 2018. Fecal samples were examined using floatat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 13 publications
5
13
0
Order By: Relevance
“…The predominance of coccidial infection followed by A . galli infection in the present findings was similar to earlier reports, from India [ 17 ], Cameroon [ 18 ], South Gujarat, India [ 9 ], and Nigeria [ 19 - 21 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The predominance of coccidial infection followed by A . galli infection in the present findings was similar to earlier reports, from India [ 17 ], Cameroon [ 18 ], South Gujarat, India [ 9 ], and Nigeria [ 19 - 21 ].…”
Section: Discussionsupporting
confidence: 92%
“…The published reports on prevalence of GIT parasites of poultry with associated risk factors from different parts of the world showed great variation (16-80%) [13][14][15][16]. The predominance of coccidial infection followed by A. galli infection in the present findings was similar to earlier reports, from India [17], Cameroon [18], South Gujarat, India [9], and Nigeria [19][20][21].…”
Section: Discussionsupporting
confidence: 87%
“…The high prevalence of multiple gastrointestinal parasites infection we recorded is expected as horses are known to harbour several species of parasites at any given time (Ehizibolo et al, 2012;Wannas et al, 2012;Umar et al, 2013;Samuel et al, 2015). The multiple gastrointestinal parasite infection reported might be attributed to the animal grazing preference, favourable climatic conditions and rate of environmental contamination with viable helminth eggs and sporulated oocysts at a particular time, which to a great extent can determine the establishment of mixed infection (Ola-Fadunsin et al, 2019). Contrary to expected outcome that foals and young horses are more susceptible to Eimeria infections compared to adult horses (Effat et al, 2014;Gülegen et al, 2016;Taylor et al, 2016;Dubey & Bauer, 2018), we observed that the prevalence of Eimeria infections increased with age.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, in Phillippines, Ilorin and Maiduguri, Nigeria reports of a lower prevalence of 43.2%, 32.83% and 31.8% of Eimeria infection in poultry were recorded [18,19,20]. Also, very lower prevalence of 3.9% and 7.7% of Eimeria spp has be reported by [21,22] among domestic fowl.…”
Section: In Comparison Of Broilers and Layers Affected Bymentioning
confidence: 98%